1998
DOI: 10.1111/j.1471-0528.1998.tb10150.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative serum level of tumour‐associated trypsin inhibitor and residual turnour size as prognostic indicators in Stage III epithelial ovarian cancer

Abstract: Objective To evaluate the use of the pre-operative tumour-associated trypsin inhibitor (TATI) level and residual tumour size at primary surgery as a prognostic indicators for patients with Stage 111 epithelial ovarian cancer.Design Retrospective cohort study. Main outcome measures Cumulative five-year survival, pre-operative serum TATI level and residual tumour size.Results Surgery was optimal (residual tumour size I 2 cm) in 55 patients and suboptimal (residual tumour size > 2 cm) in 43. Pre-operative TATI le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
(20 reference statements)
4
24
0
Order By: Relevance
“…We have earlier shown that elevated preoperative serum TATI concentrations predict adverse prognosis in patients with stage III and IV epithelial ovarian cancer (3,31). The results of the present study confirm these findings, and they additionally show that immunohistochemical expression of TATI also is a strong prognostic factor independent of tumor stage, grade, and histological type.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We have earlier shown that elevated preoperative serum TATI concentrations predict adverse prognosis in patients with stage III and IV epithelial ovarian cancer (3,31). The results of the present study confirm these findings, and they additionally show that immunohistochemical expression of TATI also is a strong prognostic factor independent of tumor stage, grade, and histological type.…”
Section: Discussionsupporting
confidence: 81%
“…The strong prognostic value of TATI expression in ovarian cancer tissue appears to explain our earlier findings showing that serum TATI predicts adverse survival in epithelial ovarian cancer (3,30,31). Serum TATI correlated with prognosis in advanced ovarian cancer also in this study, but an elevated serum concentration of trypsin-2-API was a prognostic factor both among all patients and those with advanced disease.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Early studies showed that SPINK1 in urine is a promising marker for diagnosis of ovarian cancer (13,14 ). As a diagnostic marker for ovarian cancer, serum SPINK1 was shown to be inferior to cancer antigen 125 (CA125) but superior as a prognostic marker (15 ). CA125 is the most widely studied marker for ovarian cancer.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…TATI is expressed together with trypsinogen by several tumours and cancer cell lines (Stenman et al, 1991). TATI in serum has been used as a tumour marker for mucinous ovarian cancer and it is a prognostic factor in stage III epithelial ovarian cancer (Venesmaa et al, 1998).…”
mentioning
confidence: 99%